179 Healthcare superheroes need rescue during pandemics. (16th November 2020) - Sriharan, Abi; Ratnapalan, Savithiri; Lupea, Doina; Tricco, Andrea
Abstract : The COVID-19 pandemic has placed extraordinary pressure on an already strained healthcare workforce (HCWs). Public health measures, such as prolonged periods of social isolation, unexpected employment disruptions, school closures, financial distress, and changes to routine, are having an unprecedented negative impact on mental well-being. Unaddressed stress and burnout can lead to depression, suicidal ideation and substance abuse. We conducted a review of the literature (a) to synthesize the common triggers of stress, burnout and depression faced by HCWs during the COVID-19 pandemic and (b) to identify interventions at the individual, organizational and systemic levels that can support the well-being of HCWs during a pandemic. A systematic search of literature databases was conducted from 2003 to June 2020. We included review articles that reported on stress, burnout and depression in HCWs; that primarily focused on women; and that included the percentage or number of women surveyed. Of the 2, 803 papers found, 31 were included. Our preliminary findings show that HCWs are at increased risk for stress, burnout and depression during the COVID-19 pandemic. These negative outcomes are triggered by individual-level factors such as gender, family status and lack of social support; organizational-level factors such as high workload and access to PPE;, and systemic-level factors such as prevalence of COVID-19, rapidly changing public health guidelines and a lack of recognition at work. There is a limited amount of evidence on effective interventions that prevent anxiety, stress, burnout and depression during a pandemic. Preliminary findings of causes of increased stress and mental health issues suggest possible strategies healthcare organizations can use to address modifiable factors such as ongoing training to increase confidence in caring for COVID-19 patients, clear infection control guidelines and sufficient PPE and optimization of working conditions for HCWs.